Judicial Legislations and the Tribal Claims System in the Royal Period: A Documentary Study - Ahmed Abdul Wahid Abdul Nabi (College of Education for Women, 2021)
The present research tackles a number of historical facts and incidents with a purely legal dimension in an important stage in the contemporary history of Iraq, especially the era of the British occupation. This resulted in innumerable social, political and legal problems, particularily the judicial legislation problems in Iraq. These legislations included a set of civil laws and in force governmental procedures that will be discussed historically by examining documents issued by the Ministries of Justice and Interior Affairs in the governments of monarchy for the period from 1921-to-1958. The data of the present paper relied on the Iraqi Library and Archives, (hence DKW). The study adopted the narrative historical methodology when investigating the judicial legislations in the royal era from 1921-to-1958. The scale adopted was the contemporary measurement and evaluation in the Iraqi contemporary history. Finally, the results revealed that the history of the penal procedures in the royal era was those multiple attempts to reconcile between the two types of penal procedures that represent the history of the relationship between the individual and the state. Such legislations were set according to the circumstances of each country and to the level of its intellectual, social, political and human development to serve primarily the interests of the British occupation, and  fulfill the desires of the influential class in the royal era. Because these legislations and laws were not based on modern scientific theories, many people were wronged, including the judicial authority and legal clerks who complained from their implementation and their continual application on Iraq for all this period.